Foundations in evolutionary cognitive neuroscience - Platek, Steven M.; Shackelford, Todd K. (Todd Kennedy), 1971- (Cambridge, UK ; New York : Cambridge University Press, 2009)
(Publisher-supplied data) This book is an introduction to the emerging field of evolutionary cognitive neuroscience, a branch of neuroscience that combines the disciplines of evolutionary psychology and cognitive neuroscience. It outlines the application of cognitive neuroscientific methods (e.g., functional magnetic resonance imaging, transcranial magnetic stimulation, magneto- and electroencephalography, and the use of neuropsychiatric and neurosurgical patients) to answer empirical questions posed from an evolutionary meta-theoretical perspective. Chapters outline the basics of cognitive evolution and how the methods of cognitive neuroscience can be employed to answer questions about the presence of evolved cognitive adaptations. Written for graduate students and researchers, the book presents the major topics of study undertaken by evolutionary cognitive neuroscientists - such as language evolution, intelligence and face processing - and serves as a primer upon which to base further study in the discipline.
Introduction to evolutionary psychology : a Darwinian approach to human behavior and cognition / Aaron T. Goetz, Todd K. Shackelford and Steven M. Platek -- The evolution of general fluid intelligence / David C. Geary -- The role of a general cognitive factor in the evolution of human intelligence / James J. Lee -- Where there is an adaptation, there is a domain : the form-function fit in information processing / H. Clark Barrett -- Invention and community in the emergence of language : insights from new sign languages / Michael A. Arbib -- Origins of the language : correlation between brain evolution and language development / Alfredo Ardila -- The evolutionary cognitive neuropsychology of face preferences / Anthony C. Little and Benedict C. Jones -- Sex differences in the neural correlates of jealousy / Hidehiko Takahashi and Yoshiro Okubo.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cognitive neuroscience; Brain -- Evolution; Evolutionary psychology; Neurowetenschappen; Cognitiewetenschap; Evolutionary psychology; Neurowissenschaften; Evolutionspsychologie; Kognitive Psychologie; Brain -- physiology; Cognition -- physiology; Biological Evolution; Cognitive Science; Neurosciences; SCIENCE / Cognitive Science; Aufsatzsammlung; Electronic books